The Impact of Digital Marketing on Prospective Students’ University Choice: Evidence from UDB Surakarta - Alfin Yoga Kharisma; Gita Agzumi (Eastasouth Institute, 2026)
Digital transformation has reshaped the way higher education institutions market their educational services. This study aims to analyze the influence of digital marketing on prospective students’ decisions in choosing Universitas Duta Bangsa (UDB) Surakarta. A quantitative approach was employed using a survey method involving 300 prospective students and newly enrolled students. The digital marketing variable was measured through the dimensions of social media, university website, digital content, and online advertising, while the university choice decision was measured through enrollment intention, institutional preference, and confidence in the selected choice. Regression analysis indicates that digital marketing has a positive and significant effect on prospective students’ decisions. These findings reinforce contemporary digital marketing research, which highlights that digital interaction, trust in online content, and online experiences are key determinants in young people’s decision-making processes. This study provides theoretical contributions to digital-based higher education marketing and offers practical implications for student recruitment strategies in private universities.